A novel Hercynite‐supported tetradentate Schiff base complex of manganese catalyzed one‐pot annulation reactions. (14th October 2022) - Mohammadi, Masoud; Ghorbani‐Choghamarani, Arash
Abstract : The present study is the first report on the synthesis and catalytic performance of Hercynite nanoparticles capped with a novel Schiff base–manganese(II) complex brought from a synthetic procedure. The solid support and the catalyst were characterized using various analytical techniques. The characterization results suggest excellent dispersibility, stability, high Mn content under the catalyst surface, and small size of catalyst, which leads to excellent catalytic activity and selectivity. Moreover, the catalyst proved to be sustainable and recyclable for rapid synthesis of various chromene‐ and pyran‐annulated heterocycles under ambient conditions. The effect of various crucial catalytic parameters was investigated and optimized. The scope of the reaction was extended to various aryl aldehydes and keto–enol tautomeric pairs (2‐hydroxy‐1, 4‐naphthoquinone or dimedone), and the corresponding 2‐amino‐3‐cyano‐4 H ‐chromene and 2‐amino‐3‐cyano‐4 H ‐pyran products were obtained with excellent yield (82–99%) and at low reaction time (10–115 min). Significantly, the catalyst indicated magnetic, cost‐effective, and nontoxic properties, which result in having high recycling efficiency (5 cycles). Abstract : Silica‐modified Hercynite‐coated Schiff base–manganese complex [Hercynite@SiO2 –Schiff base–Mn(II)] is synthesized and characterized as an efficient and heterogeneous recoverable Hercynite‐supported catalytic complex for the synthesis of 2‐amino‐3‐cyano‐4 H ‐chromene and 2‐amino‐3‐cyano‐4 H ‐pyran derivatives by one‐pot direct Knoevenagel condensation–Michael addition–Thorpe–Ziegler‐type cyclization sequences under green conditions.